Accuracy of the Physiological and Operative Severity Score for the enUmeration of Mortality and morbidity score and the Nottingham risk score in hip fracture patients in Sweden — A prospective observational study. Issue 8 (23rd April 2018) - Jonsson, M. H.; Bentzer, P.; Turkiewicz, A.; Hommel, A.
Abstract : Background: Little is known about accuracy of common risk prediction scores in elderly patients suffering from hip fractures. The objective of this study was to investigate accuracy of the Physiological and Operative Severity Score for the enUmeration of Mortality and morbidity (POSSUM) score, Portsmouth‐POSSUM (P‐POSSUM) score and the Nottingham Hip Fracture Score (NHFS) for prediction of mortality and morbidity in this patient group. Methods: This was a prospective single centre observational study on 997 patients suffering out‐of‐hospital cervical, trochanteric or subtrochanteric fracture of the neck of the femur. Calibration and discrimination was assessed by calculating the ratio of observed to expected events (O:E) and areas under receiver operating characteristics curves (ROC). Results: The 30‐day mortality was 6.2% and complications, as defined by POSSUM, occurred in 41% of the patients. Overall O:E ratios for POSSUM, P‐POSSUM and NHFS scores for 30‐day mortality were 0.90, 0.98, and 0.79 respectively. The models underestimated mortality in the lower risk bands and overestimated mortality in the higher risk bands. In contrast, POSSUM predicted morbidity well with O:E ratios close to unity in most risk bands. The areas under the ROC curves for the scoring systems was 0.60‐0.67. Conclusion: The POSSUM score and NHFS show moderate calibration and poor discrimination in this cohort. The results suggest that mortality and morbidity in hip fracture patients are largely dependent on factors that are not included in these scores.